2016
DOI: 10.1124/mol.116.106112
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Novel GPR39 Agonists Allosterically Modulated by Zinc

Abstract: In this study, we identified two previously described kinase inhibitors-3-(4-chloro-2-fluorobenzyl)-2-methyl-N-(3-methyl-1H-pyrazol-agonists by unbiased small-molecule-based screening using a b-arrestin recruitment screening approach (PRESTO-Tango). We characterized the signaling of LY2784544 and GSK2636771 and compared their signaling patterns with a previously described "GPR39-selective"at both canonical and noncanonical signaling pathways. Unexpectedly, all three compounds displayed probe-dependent and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 89 publications
(72 reference statements)
2
76
0
Order By: Relevance
“…Activation of Gpr39 induces the release of Ca 2+ via the IP 3 pathway. The receptor may play a role in depression, and as a specific and direct sensor of Zn 2+ , in many physiological functions where the cation is involved such as synaptic transmission (Popovics and Stewart, 2011 ; Sato et al, 2016 ). Kisspeptin, encoded by the Kiss1 gene, is considered to have an emerging role in the neuroendocrine regulation of reproduction and puberty (de Roux et al, 2003 ; Seminara, 2006 ; Kauffman et al, 2007 ; Colledge, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Gpr39 induces the release of Ca 2+ via the IP 3 pathway. The receptor may play a role in depression, and as a specific and direct sensor of Zn 2+ , in many physiological functions where the cation is involved such as synaptic transmission (Popovics and Stewart, 2011 ; Sato et al, 2016 ). Kisspeptin, encoded by the Kiss1 gene, is considered to have an emerging role in the neuroendocrine regulation of reproduction and puberty (de Roux et al, 2003 ; Seminara, 2006 ; Kauffman et al, 2007 ; Colledge, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated an unexpected role of zinc at GPR39, a member of the ghrelin peptide receptor family. In addition to activation of GPR39, which is described as a Zn 2+ -sensing receptor, zinc also allosterically enhanced intracellular signaling induced by two novel small-molecule agonists of GPR39: LY2784544 and GSK2636771 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear if the pharmacokinetics of Zn 2+ with GPR39 support it as a physiological agonist of the receptor. It is more likely that zinc modulates receptor activity based on studies characterizing synthetic GPR39 agonists (17). Furthermore, Zn 2+ is known to be an allosteric modulator for multiple receptors and ion channels (31).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc has been reported to be either a GPR39 agonist (14) or an allosteric modulator for synthetic ligands of the receptor (17). Therefore, we first tested the effect of Zn 2+ alone in mVSMCs and found that it increased intracellular calcium at concentrations ≥20 M ( Fig 3E) and had no effect at concentrations between 1-10 M (Fig 3F).…”
Section: Zinc Sensitizes Gpr39 To 1415-eet and 15-hetementioning
confidence: 95%